DRIVING SUSTAINABLE HOMESTAY PERFORMANCE THROUGH DRONE TECHNOLOGY AND TAKAFUL INTEGRATION - Ramlan, Nurul Liyana; Zulkifli, Ahmad Farouk; Antara, Purnomo M; Ali, Asiah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The increasing frequency of natural disasters and the growing importance of ethical risk-sharing mechanisms have led to the emergence of innovative solutions in the tourism and insurance sectors. This study examines the integration of drone technology and takaful (Islamic insurance) in enhancing the performance and sustainability of homestay businesses in Malaysia. Drawing on qualitative data, including expert interviews and a disaster simulation exercise, this paper explores the potential of drones to improve post-disaster response, property inspections and marketing efficiency. Concurrently, it investigates how takaful supports homestay operators by offering Shariah-compliant risk mitigation. Findings highlight that the use of drones enhances claim accuracy and speeds up the compensation process, aligning with the maqasid al-shariah principle of community welfare. The research also identifies operational, financial and regulatory challenges that need to be addressed. In addition, the study applies the Technology Acceptance Model (TAM) and Technological, Organizational and Environmental (TOE) framework to examine the adoption of drone technology among homestay and takaful stakeholders. Therefore, this paper proposes strategic pathways for takaful operators and homestay businesses to collaborate, advancing ethical, technology-driven solutions for a resilient tourism sector.